2021
DOI: 10.1038/s41389-021-00321-2
|View full text |Cite
|
Sign up to set email alerts
|

CARD10 cleavage by MALT1 restricts lung carcinoma growth in vivo

Abstract: CARD-CC complexes involving BCL10 and MALT1 are major cellular signaling hubs. They govern NF-κB activation through their scaffolding properties as well as MALT1 paracaspase function, which cleaves substrates involved in NF-κB regulation. In human lymphocytes, gain-of-function defects in this pathway lead to lymphoproliferative disorders. CARD10, the prototypical CARD-CC protein in non-hematopoietic cells, is overexpressed in several cancers and has been associated with poor prognosis. However, regulation of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…MALT1 paracaspase was recently identified as a novel negative regulator of LUBAC-mediated signaling, whereby it cleaves HOIL1 to destabilize LUBAC assembly (37)(38)(39). As MALT1 has 12 substrates reported to date, and each regulates NF-kB or other signaling pathways differently (41)(42)(43), it is difficult to study the specific effects of cleavage of individual substrates by simply inhibiting MALT1 protease activity or genetically knocking-out/ down MALT1. To directly investigate the role of MALT1dependent cleavage of HOIL1 in immunity and physiology, we generated a non-cleavable version of HOIL1 (HOIL1-R/K) and stably expressed this construct in primary HOIL1-deficient patient fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…MALT1 paracaspase was recently identified as a novel negative regulator of LUBAC-mediated signaling, whereby it cleaves HOIL1 to destabilize LUBAC assembly (37)(38)(39). As MALT1 has 12 substrates reported to date, and each regulates NF-kB or other signaling pathways differently (41)(42)(43), it is difficult to study the specific effects of cleavage of individual substrates by simply inhibiting MALT1 protease activity or genetically knocking-out/ down MALT1. To directly investigate the role of MALT1dependent cleavage of HOIL1 in immunity and physiology, we generated a non-cleavable version of HOIL1 (HOIL1-R/K) and stably expressed this construct in primary HOIL1-deficient patient fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…With 18 untested candidates in the top 40 proteins ranked by GO-2-Substrates (Supplementary Table 1 ), we predict that approximately 50 % will likely be new MALT1 substrates, a notable success rate. Indeed, during the preparation of this manuscript, CARD10 (rank 14) was validated as a novel MALT1 substrate [42] . To our knowledge, our work represents the first method to rank human proteins as potential MALT1 substrates by proteome-wide analysis.…”
Section: Resultsmentioning
confidence: 99%
“…During the preparation of this manuscript, Israël and coworkers [42] described the MALT1 cleavage of CARD10. Despite an unusual Ala at P 2 in its MALT1 cleavage site (Leu-Leu- Ala -Arg 587 ↓Gly), GO-2-Substrates correctly ranked CARD10 as an exceptionally strong candidate substrate—mainly due to its functional similarity to known substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas most studies describe a tumor-promoting role for MALT1, a recent study suggests that MALT1 can also act as a tumor suppressor. In the lung cancer cell line A549, MALT1 cleaves the C10BM complex member CARD10 after the arginine residue at position 587, thereby dampening its capacity to activate NF-κB [ 95 ]. In this manner, the cleavage of CARD10 by MALT1 acts as a negative feedback mechanism that limits the signaling potential and pro-tumorigenic role of CARD10.…”
Section: The Role Of the Cbm Complex In Solid Tumorsmentioning
confidence: 99%
“…This is also reflected in the observation that A549 knock-in (KI) cells expressing the cleavage-deficient R587A CARD10 variant exhibit a growth advantage, increased angiogenesis, and tumorigenic potential upon i.v. injection in mice [ 95 ]. The authors identified IL-6 as the main cytokine upregulated in the A549-KI cells, suggesting that cleavage of CARD10 by MALT1 is important to limit IL-6 signaling and to suppress tumorigenesis.…”
Section: The Role Of the Cbm Complex In Solid Tumorsmentioning
confidence: 99%